The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s002185962100037x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of compound treatment of Aspergillus oryzae and fibrolytic enzyme on in vitro degradation, gas production and fermentative profile of maize silage and sugarcane silage

Abstract: The present study was conducted to evaluate the effect of a live culture of Aspergillus oryzae (A; CCT4359) and fibrolytic enzyme (E; Fibrozyme Alltech Inc.) on fibre digestibility by a gas production bioassay and in vitro degradation of maize silage and sugarcane silage. A completely randomized design trial was performed to evaluate: A doses (0, 20, 60 and 100 mg/l), E doses (0, 160, 320 and 480 mg/l) and roughage source (R; maize and sugarcane silage) in a 4 × 4 × 2 factorial arrangement. The inclusion of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…Wang et al 11 showed that supplementation with fibrolytic enzymes tended to increase feed intake of bull calves aged 46 to 90 days. The discrepancy between our results and those of other researchers could be due to the method of administration of fibrolytic enzymes (direct administration into the starter feed versus pretreatment of the forage with fibrolytic enzymes), the composition of the basal feed, especially fiber sources or fiber content, which affect the activity and stability of rumen enzymes 14 . The lower concentration of NDF and higher digestibility of NDF should improve feed intake.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Wang et al 11 showed that supplementation with fibrolytic enzymes tended to increase feed intake of bull calves aged 46 to 90 days. The discrepancy between our results and those of other researchers could be due to the method of administration of fibrolytic enzymes (direct administration into the starter feed versus pretreatment of the forage with fibrolytic enzymes), the composition of the basal feed, especially fiber sources or fiber content, which affect the activity and stability of rumen enzymes 14 . The lower concentration of NDF and higher digestibility of NDF should improve feed intake.…”
Section: Discussioncontrasting
confidence: 99%
“…Both supplements, fibrolytic enzymes and probiotics, have the potential to modulate rumen fermentation and improve fiber digestibility, animal performance, and feed conversion efficiency. Some researchers have investigated the synergistic interaction between these two additives in in vitro and in vivo studies 12 14 . Despite conflicting results in in vitro studies, Malik and Bandla 12 reported that the combination of probiotics and fibrolytic enzymes had a reciprocal beneficial effect on rumen fermentation and improved growth performance and feed efficiency of growing buffalo calves.…”
Section: Introductionmentioning
confidence: 99%